A Young Planetary Mass Companion to the Nearby M Dwarf VHS J125601.92-125723.9. Issue Volume 10:Issue S314(2015) (November 2015) - Gauza, B.; Béjar, V. J. S.; Pérez-Garrido, A.; Osorio, M. R. Zapatero; Lodieu, N.; Rebolo, R.; Pallé, E.; Nowak, G.
Abstract: We have recently identified a young, very red ( J − Ks = 2.47 mag) late L-type companion at 8.06" ± 0.03" ( 102 AU) from a previously unrecognized M dwarf. We determined the parallactic distance of the system to be 12.7±1.0 pc. Non-detection of lithium and the kinematics of the primary allowed us to constrain the age of the system in the range of 150–300 Myr. By comparison with theoretical evolutionary models we derived a mass of 73 +20 −15 M Jup for the primary, at around the substellar mass regime and 11.2 +9.7 −1.8 M Jup for the secondary, near the deuterium burning mass limit.